Development and validation of a dynamic primary standard for unsteady liquid flow calibration. (April 2022) - Ogheard, Florestan; Noël, Jean; Granger, Pascal; Gassette, Carl-André
Abstract: LNE-CETIAT liquid flow laboratory is the French Designated Institute for liquid water flow rate from 1 g h −1 to 50 t h −1 . Historically, its primary standards are based on the flying start and stop gravimetric method. The best relative expanded uncertainty for liquid mass flow rate is 0.05% ( k = 2 ). In the scope of the Joint Research Project Metrowamet and its mission to maintain and develop the French standards for liquid flow, LNE-CETIAT has developed and validated a dynamic primary standard for unsteady liquid flow calibration. This paper will first present the developped system, which is composed of a dynamic flow generator and a dedicated measuring system together with its own software for data acquisition and processing. The validation, realized by intra and inter-laboratory comparisons for static and dynamic flows, is presented in the third chapter. Finally, the validation of the measurement and calibration capabilities, based on internal tests and inter-laboratory comparisons are presented. Highlights: Flow and water meters are calibrated under steady and controlled flow conditions. Flow and water meters are often used in unsteady, uncontrolled flow conditions. A dynamic calibration method has been developed for dynamic liquid flow calibrations. Experimental validation shows an associated relative uncertainty of 0.2% (k = 2) under dynamic flow conditions. The method can be adapted to higher and lower flow rates and to other physical quantities.